Capacitive Pressure Sensor With Integrated Signal-Conversion Circuit for High-Temperature Applications - Chen Li; Boshan Sun; Pengyu Jia; Yanan Xue; Mangu Jia; Jijun Xiong (IEEE Access, 2020)
In this paper, a capacitive pressure sensor for high-temperature application is proposed. This sensor includes three parts: a capacitive pressure-sensitive chip fabricated from green tapes using lamination technology, a C-V conversion circuit fabricated using high-temperature-resistant electronic components and a PCB board, and a thermal-insulation shell fabricated from a high-temperature-resistant alloy and aerogel. Due to the aerogel, which is a thermal-insulation material, being filled between the circuit board and the rear-end shell, when the air intake temperature reaches 350°C, the temperature transmitted to the C-V conversion circuit board can be kept below 60°C; this ensures normal operation of the C-V converter circuit. The developed sensor can record pressure values from room temperature to 350 °C. According to the pressure-voltage curves at different temperatures obtained from tests, the sensor's sensitivity is 38 mV/bar, and its repeatability error is less than 1.948%. The results show that the proposed sensor has a high operating temperature and is more reliable and linear than existing sensors.